A CONCEPTUAL EXPLORATION OF DEMOGRAPHIC VARIABLES AND TEACHERS’ JOB SATISFACTION IN EDUCATION PERSPECTIVES - Nor Roselidyawaty Mohd Rokeman; Che Ghani Che Kob; Mohd Fadzlee Untong (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This concept review paper delves into the complex dynamics between job satisfaction, demographic diversity among employees, and job performance within educational sector organizations. Despite a wealth of empirical studies and theoretical literature suggesting correlations between demographic factors as moderators and job satisfaction, the evidence remains fragmented and inconclusive. This concept paper aims to bridge this gap by explore the moderating role of demographic factors in shaping the relationship between job satisfaction, considering the significant variability in correlation strength across studies. The findings reveal that the nature and strength of these associations vary considerably based on the organizational context, particularly regarding how demographic diversity in management influences employee job satisfaction within educational settings. Through analysis of data gathered from various public sector environments, we demonstrate that gender, age, length of service, marital status, work experience, level of education and school location attributes significantly impact employee job satisfaction, particularly within educational contexts. This study highlights the necessity of integrating demographic factors into future research on job satisfaction, as it builds upon a robust empirical and theoretical foundation supporting these relationships. As organizations endeavour to enhance employee well-being and performance, understanding the intricate interplay between demographic diversity and job satisfaction becomes imperative for effective management and policy formulation.